CT-Based Measurements of Facial Parameters of Healthy Children and Adolescents in Thailand - Jullabussapa, N.; Khwanngern, K.; Pateekhum, C.; Angkurawaranon, C.; Angkurawaranon, S. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Facial parameters are used for evaluating normal growth patterns, diagnosing patients with craniofacial abnormalities, and planning surgical procedures. However, these parameters vary by ethnicity and race. This study aims to describe soft-tissue and bony facial parameters based on CT of healthy pediatric and adolescent patients in Thailand.MATERIALS AND METHODS: CT imaging of the brain, orbit, facial bones, and neck was performed at Maharaj Nakorn Chiangmai Hospital, in patients from birth to 19 years old. Patients with known syndromic disease, craniofacial syndrome, facial trauma and/or infection, and previous surgery that deformed the study area were excluded. The key points of measurement were soft-tissue intercanthal, bony interorbital, and bony lateral orbital distances.RESULTS: There were 932 patients: 554 males (59.4%) and 378 females (40.6%). Facial parameters rapidly increased in the first 2 years of life. Significant differences in these parameters between the males and females were found at the age of ≥15 years. However, ratios of the interorbital to the lateral orbital distance were generally consistent among age groups in both sexes, at 0.25.CONCLUSIONS: This study, in Thailand, provides detailed age- and sex-specific normative data of the craniofacial measurements in children and adolescences based on CT imaging. These data can be used for evaluating individual patients with craniofacial abnormalities as well as determining the treatment in Thai and Asian populations, in whom craniofacial abnormalities, for example, frontoethmoidal encephalomeningocele, are common.ICintercanthalIOinterorbitalLOlateral orbitalSDstandard deviation